Effect of a Specialized Nursing Subject Assignment on Perceived Knowledge and Skills to Care for Drug Users - Villegas-Pantoja, Miguel A.; Moreno-Cruz, Mildred Astrid; Méndez-Ruiz, Martha Dalila; Reyes Sánchez, Carlos (Investigación y educación en enfermería, 2024)
Objective. To identify the effect of a specialized subject on addictions on the knowledge and skills perceived by undergraduate nursing students to care for drug users. Methods. This was a pre-experimental study of a single group with post- and pre-test measurements. The study included a sample of 59 students registered in the seventh semester in a public university in northeastern Mexico, who received 64 theoretical hours of the subject assignment “Nursing and addictions”, which was taught in face-to-face classes by professor nurses with training in the care of addictions. The emphasis was theoretical, where strategies, like clinical cases, screening instruments, and audiovisual material were used. Information was collected about sociodemographic data and the scale by Happel et al., of knowledge and perceived skills on the care of alcohol and other drug users was applied. Results. The post-test registered higher scores in the subscales of overall knowledge on substance use (W = –4.532, p < 0.001), perceived knowledge on management of drug users (W = –5.909, p < 0.001), and perceived competences to care for alcohol and drug users (t = –8.000, p < 0.001). Conclusion. The subject assignment analyzed contributed to increasing knowledge by nursing students regarding the phenomenon of addictions. As for perceived competences, although these increased significantly, they would have to be demonstrated in light of practical scenarios that confirm their persistence and impact on the quality of care.